Efek Air Laut dan Bahan Mineral Terhadap Sifat Kimia Tanah, Pertumbuhan dan Produksi Padi Pada Tanah Gambut - Lila Wulandari; Sarifuddin Sarifuddin; Benny Hidayat (Universitas Sumatera Utara, 2014)
The objective of this research is to study the effect of sea water and mineral materials on soilchemical properties, growth and production of rice in peat soils. This research was conducted atgreen house and samples analyzed at soil chemical and fertility laboratory and research andtechnology laboratory. This research used factorial randomized block design with 2 factorstreatments consist of sea water and mineral materials (volcanic material, steel slag, dolomite, andcalx) with 3 replications. Volume of sea water added were 0 ml (+ 1000 ml fresh water) per pot,250 ml (+ 750 ml fresh water) per pot and 500 ml (+ 500 ml fresh water) per pot. Dosage ofvolcanic material, steel slag, dolomite, and calx are 250 g/pot, 50 g/pot, 50 g/pot, and 250 g/pot.The result showed that application volume of sea water influenced significantly increase ofelectrical conductivity, ratio C/N and empty grains but not significantly effect on soil acidicity,natrium, kalium, calcium, and magnesium exchangeable, cation exchange capacity, base saturation,organic carbon, total nitrogen, bulk dencity, number of tillers, and productive tillers per clump, andweight of 1000 grain. Application of mineral materials (volcanic sand, steel slag, dolomite, andcalx) increase significantly of soil acidicity, cation exchange capacity, organic carbon, and weight1000 grain but not significant on natrium exchangeable, total nitrogen and bulk dencity.Keyword: sea water, volcanic sand, steel slag, dolomite, calx, peat, rice